2018
DOI: 10.1021/acssuschemeng.8b01930
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Catalytic Biorefining of Hardwood Biomass to Methylated Furans and Depolymerized Technical Lignin

Abstract: A robust method is needed to achieve high yield all-catalytic conversion of recalcitrant lignocellulosic biomass to transportation fuels while maximizing carbon utilization from raw substrates. To accomplish this, we developed an integrated strategy that combines homogeneous and heterogeneous reactions with a treatment-extraction step to coproduce 2-methylfuran (MF) and 2,5-dimethylfuran (DMF) directly from hardwood poplar while maintaining high catalyst activity. In the first step, poplar wood chips were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…The extracted lignin contains a minimal amount of ashes and sugars for more effective catalytic upgrading, serving as the primary lignin feedstock to many of the catalytic systems mentioned herein. Cosolvent systems, such as ethanol–water, methanol–water, acetone–water, formic acid–water, THF–water, and gamma‐valerolactone (GVL)–water, have been shown to produce high‐quality lignin feedstocks. The lignin is precipitated out and has a higher purity and less structural changes than that of acid and base pretreated lignin .…”
Section: Pretreatment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracted lignin contains a minimal amount of ashes and sugars for more effective catalytic upgrading, serving as the primary lignin feedstock to many of the catalytic systems mentioned herein. Cosolvent systems, such as ethanol–water, methanol–water, acetone–water, formic acid–water, THF–water, and gamma‐valerolactone (GVL)–water, have been shown to produce high‐quality lignin feedstocks. The lignin is precipitated out and has a higher purity and less structural changes than that of acid and base pretreated lignin .…”
Section: Pretreatment Methodsmentioning
confidence: 99%
“…At a high level, catalytic processing can be categorized as either homo‐ or heterogeneous that can be differentiated by the use of catalysts that are either soluble or insoluble in the liquid medium, respectively, during the intended reaction. Both types are useful for processing biomass and biomass‐derived intermediates and a combined strategy is often proposed to take advantage of the merits of both . Homogeneous catalysis for biomass upgrading primarily addresses the challenges of the direct processing of raw biomass feedstocks to drive sufficient biomass deconstruction by solubilization, hydrolysis, and dehydration to liquid chemical intermediates, such as sugars, furfurals, oxo acids, polyols, and depolymerized technical lignins .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline Populus (trichocarpa x deltoides) was harvested from Oak Ridge National Laboratory (ORNL) and shipped to National Renewable Energy Laboratory (NREL) for drying, debarking, and size-reduction. Extractives were removed by an ethanol/toluene Soxhlet extraction, and the composition of the poplar was measured to be ∼45% glucan, ∼15% xylan, and ∼22% Klason lignin via a NREL procedure (Seemala et al, 2018;Sluiter et al, 2008). Hydrated ferric chloride was purchased from Sigma Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…During CELF pretreatment, 85%-90% of the lignin can be solubilized into the co-solvent mixture, and an ash-free and sugar-free product known as CELF lignin can be obtained by precipitation after boiling off the THF (Cai et al, 2014(Cai et al, , 2013. Recent studies have found that CELF lignin drastically reduces molecular weight from native lignin while minimizing competing cross-condensation reactions Thus, CELF process could serve as a unique tool to produce highly fractionated lignin (Meng et al, 2018;Seemala et al, 2018).…”
Section: Introductionmentioning
confidence: 99%